Stateness and democracy in East Asia - Croissant, Aurel; Hellmann, Olli (Cambridge University Press, 2020)
Introduction : rethinking stateness and democracy in East Asia / Aurel Croissant and Olli Hellmann -- State building and democratization : the sequencing debate and evidence from East Asia / Tuong Vu -- South Korea's democracy and the legacies of the developmental state / Olli Hellmann -- Hegemony : state capacity, the quality of democracy and the legacies of the party-state in democratic Taiwan / Kharis Templeman -- Democratization interrupted : the parallel state and the demise of democracy in Thailand / Paul Chambers -- Weak state and the limits of democratization in Cambodia, 1993-2017 / Kheang Un -- The institutional roots of defective democracy in the Philippines / Erik Martinez Kuhonta and Nhu Truong -- Stateness and state capacity in post-authoritarian Indonesia : securing democracy's survival, entrenching its low quality / Marcus Mietzner -- As good as it gets? : stateness and democracy in East Timor / Aurel Croissant and Rebecca Abu Sharkh -- Stateness and democracy : evidence from East Asia and cross-regional comparisons / Aurel Croissant and Olli Hellmann.